Study Of The Development Of Fish Landing Facilities Labuhanhajihaji Base (PPI Labuhanhaji) Southern Districts Of Aceh Province Of Aceh In The Reviews Of The Use Of Facilities - Putri Dewi; Syaifuddin '; Jonny Zain (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
Fish landing place of Labuhanhaji is a place that support the economy of marine in fishiness south Aceh District. Fish landing place of Labuhanhaji is a fishiness port Type D that fu fill local resident needs. The development of PPI’s Labuhanhaji is guide well because of its strategies photon and abundant of its resources. Besides, it is supported by current transports from south Aceh District to other place as North Sumatera. The goal of this research is to understand Condon and utilization rate of the PPI. The research benefits is to give input and consider to in future development. Data is analyzed by technical utilization rate, and SWOT analyzes. The result is 26,14 %. For berth, 112,41 % to TPI 533,37 % port asin and 41 % to the depth of pot basin Kata Kunci : Fish landing Harbors, The Condition of facility, capacity